1109 Broadly Assessing Sleep Complaints In A Sample Of Patients With ADHD. (27th May 2020) - Seewald, M; Alio, C; Rosenfield, B; DiTomasso, R; Muench, A L; Rostain, A L; Ramsay, J; Klingman, K; Perlis, M L
Abstract: Introduction: It is commonly observed in clinical settings that patients with ADHD regularly present with comorbid "sleep disturbances". In the absence of broad based sleep disorders assessments, it is thought that this represents Delayed Sleep Phase Disorder (DSPD). Recently, a surveillance study was undertaken in a university-based, outpatient specialty clinic for adults with ADHD, by adding a comprehensive sleep disorders screener (SDS-CL-25) to the clinical intake procedures. These data were used to ascertain which sleep disorders symptoms are common in this clinical cohort. Methods: SDS-CL-25 data were collected in 150 subjects (93/57 male/female, mean age 32.8, age range 18-79). The SDS-CL-25 is a 25 item instrument developed to screen for 13 sleep disorders at one time (Sleep Dx symptoms are endorsed on Likert-scales; 0 [never] 4 [>5x/week]). For the purposes of this study, the percentage of subjects endorsing frequent symptomatology (sum of the percent of endorsements for columns 3 & 4)was calculated per symptom. Sums of > 20% were considered, a priori, to be of clinical significance. Results: Patients endorsed: increased fatigue (59%); SL or WASO or EMA's > 30 minutes (40%; 26%; 21%, respectively); late preferred time to bed (31%); work & school limits sleep opportunity (30%); variable time to and out of bed (27%); and snoring (21%). The average percent endorsement was 15% (range 0-59%). Conclusion: These results suggest that, consistent with clinical observations, adult patients diagnosed with ADHD frequently endorse late preferred time to bed, variable sleep wake schedules, work/school limitations on sleep opportunity, and sleep onset problems that are accompanied by daytime fatigue. This constellation of symptoms is consistent with the notion that patients with ADHD tend to have comorbid DSPD. The high prevalence of middle and late insomnia was unexpected and suggests that Insomnia Disorder (proper) may also be a feature of ADHD. Support: No support was provided for this abstract.